PENGGUNAAN “ICE BREAKING “ DALAM MENINGKATKAN KONSENTRASI BELAJAR ANAK USIA 5 - 6 TAHUN : USING “ICE BREAKING” TO IMPROVE LEARNING CONCENTRATION OF CHILDREN AGED 5 - 6 YEARS - Annisa dio Ismi; ismatul khasanah; Dwi Prasetiyawati (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2025)
The use of ice breaking to improve the learning concentration of children aged 5-6 years at Ceria Anakku Kindergaten Semarang. The background of this study is that many children aged 5-6 years experience difficulties in maintaining concentration, with many children talking to themselves while the teacher explains, asking many questions during activities, having an unfocused perspective, moving frequently, and even daydreaming. These are characteristics of low concentration in children aged 5-6 years. One of the contributing factors is the lack of innovation in learning activities provided to increase children's concentration. The purpose of this study is to describe the use of ice breaking in improving the learning concentration of children aged 5-6 years. This research is descriptive qualitative research. The data sources consist of TK B1 and TK B2 at TK Ceria Anakku, totaling 30 children. The data in this study were obtained from observations. Chapter II Documentation. The research results indicate that the use of ice breaking can improve the learning concentration of children aged 5-6 years.